A newly isolated cotton-infecting Polerovirus with cryptic pathogenicity encodes a weak suppressor of RNA silencing - Akinyuwa, Mary F.; Price, Bailee K.; Martin, Kathleen M.; Kang, Sung-Hwan (Frontiers in Agronomy, 2023)
Cotton is a multipurpose crop grown globally, including the United States. Cotton leafroll dwarf virus (CLRDV), a phloem-limited virus (Solemoviridae) transmitted by aphids, causes significant economic losses to cotton cultivation. CLRDV strains (CLRDV-typical and atypical) that were previously prevalent in other countries cause severe symptoms leading to high yield loss. Recently, a new isolate of CLRDV (CLRDV-AL) has been characterized from infected cotton plants in Alabama that are often asymptomatic and difficult to detect, implying a low titer and pathogenicity within the host. Different pathogenicity among certain strains within the same species often correlates with both environmental and molecular factors. Thus, better management and control of the vector-borne disease can be achieved by elucidating host-pathogen interaction, such as host immune response and pathogen counter-response. In this study, we demonstrate the ability of CLRDV-AL to suppress a major host defense response known as RNA silencing and compare the potency of silencing suppression to other strains of the same virus. Also, we discuss the difference in pathogenicity among them by evaluating the observations based on the amino acid variation within the functional domain. Our study provides and suggests a future direction for specifying the strategy to mitigate potential cotton disease severity.